Assessment of Knowledge, Attitudes, and Practices towards New Coronavirus (SARS-CoV-2) of Health Care Professionals in Greece before the Outbreak Period - Papagiannis, Dimitrios; Malli, Foteini; Raptis, Dimitrios G.; Papathanasiou, Ioanna V.; Fradelos, Evangelos C.; Daniil, Zoe; Rachiotis, Georgios; Gourgoulianis, Konstantinos I. (International journal of environmental research and public health, 2020)
Introduction: The ongoing severe acute respiratory syndrome (SARS)-CoV-2 pandemic has expanded globally. The aim of the current study is to investigate the knowledge, attitudes, and practices (KAP) of health care professionals in Greece towards SARS-CoV-2. Methods: From 10–25 February 2020, 500 health care workers were approached. Knowledge, attitudes, and practices towards SARS-CoV-2 were assessed via a personal interview questionnaire. For knowledge, each correct answer was given 1 point; attitudes, or concerns aimed at prevention of SARS-CoV-2 infection, and practices, or behaviors towards performing preventive practices, were assigned 1 point each. Points were summed and a score for each category was calculated. Results: A total of 461 health care workers returned the questionnaire and were included in the analysis (mean age ± SD: 44.2 ± 10.78 years, 74% females). The majority were nurses (47.5%), followed by physicians (30.5%) and paramedics (19%). The majority of subjects (88.28%) had a good level of knowledge (knowledge score equal to 4, or more). The majority of participants (71%) agreed with the temporary traveling restrictions ban. The uptake of a future vaccine against SARS-CoV-2 was estimated at 43%. Knowledge score was significantly associated with both attitudes score (p = 0.011) and practices score (p < 0.001), indicating that subjects with a high knowledge score demonstrated a more positive perception on preventive measures and would practice more preventive measures. Attitudes score was significantly associated with practices score (p = 0.009) indicating that subjects with a higher attitudes score are more likely to perform practices towards the prevention of SARS-CoV-2 transmission. Conclusion: There is a high level of knowledge concerning SARS-CoV-2 pandemic among Greek health care workers and this is significantly associated with positive attitudes and practices towards preventive health measures. The high level of knowledge of health professionals about SARS-CoV-2 may have contributed considerably to the successful management of the pandemic in Greece. Tailored educational campaigns aiming to increase the proportion of health care workers willing to accept a potential SARS-CoV-2 vaccine could be of paramount importance in future proactive vaccine educational campaigns.